In search of the holy grail of fly motion vision. (23rd September 2014) - Borst, Alexander
Abstract Detecting the direction of image motion is important for visual navigation as well as predator, prey and mate detection and, thus, essential for the survival of all animals that have eyes. However, the direction of motion is not explicitly represented at the level of the photoreceptors: it rather needs to be computed by subsequent neural circuits, involving a comparison of the signals from neighbouring photoreceptors over time. The exact nature of this process as implemented at the neuronal level has been a long‐standing question in the field. Only recently, much progress has been made in Drosophila by genetically targeting individual neuron types to block, activate or record from them. The results obtained this way indicate that: (i) luminance information from fly photoreceptors R1–6 is split into two parallel motion circuits, specialized to detect the motion of luminance increments (ON‐Channel) and decrements (OFF‐Channel) separately; (ii) lamina neurons L1 and L2 are the primary input neurons to these circuits (L1 → ON‐channel, L2 → OFF‐channel); and (iii) T4 and T5 cells carry their output signals (ON → T4, OFF → T5).